Cultural Entrepreneurship: Die Besonderheiten des Gründungsverlaufes – eine Interviewstudie in der Kultur- und Kreativwirtschaft - Heinze, Anne (transcript, 2018)
Cultural entrepreneurs play a fundamental role for medium-sized companies in the cultural and creative industries. They assume entrepreneurial responsibility in a cultural state which has thus far been predominantly publicly financed.